Soil Texture, Sampling Depth and Root Hairs Shape the Structure of ACC Deaminase Bacterial Community Composition in Maize Rhizosphere - Gebauer, Lucie; Bouffaud, Marie-Lara; Ganther, Minh; Yim, Bunlong; Vetterlein, Doris; Smalla, Kornelia; Buscot, François; Heintz-Buschart, Anna; Tarkka, Mika T. (Frontiers in Microbiology, 2021)
Preservation of the phytostimulatory functions of plant growth-promoting bacteria relies on the adaptation of their community to the rhizosphere environment. Here, an amplicon sequencing approach was implemented to specifically target microorganisms with 1-aminocyclopropane-1-carboxylate deaminase activity, carrying the acdS gene. We stated the hypothesis that the relative phylogenetic distribution of acdS carrying microorganisms is affected by the presence or absence of root hairs, soil type and depth. To this end, a standardized soil column experiment was conducted with maize wild type and root hair defective rth3 mutant in the substrates loam and sand, and harvest was implemented from three depths. Most acdS sequences (99%) were affiliated to Actinobacteria and Proteobacteria, and the strongest influence on the relative abundances of sequences were exerted by the substrate. Variovorax, Acidovorax and Ralstonia sequences dominated in loam, whereas Streptomyces and Agromyces were more abundant in sand. Soil depth caused strong variations in acdS sequence distribution, with differential levels in the relative abundances of acdS sequences affiliated to Tetrasphaera, Amycolatopsis and Streptomyces in loam, but Burkholderia, Paraburkholderia and Variovorax in sand. Maize genotype influenced the distribution of acdS sequences mainly in loam and only in the uppermost depth. Variovorax acdS sequences were more abundant in WT, but Streptomyces, Microbacterium and Modestobacter in rth3 rhizosphere. Substrate and soil depth were strong and plant genotype a further significant single and interacting drivers of acdS carrying microbial community composition in the rhizosphere of maize. This suggests that maize rhizosphere acdS carrying bacterial community establishes according to the environmental constraints, and that root hairs possess a minor but significant impact on acdS carrying bacterial populations.